Systematic Review on Prevention and Treatment of Nipple Pain and Fissure: Are They Curable - Azin Niazi; Vafa Baradaran Rahimi; Sina Soheili-Far; Nafiseh Askari; Pouria Rahmanian-Devin; Zahra Sanei-Far; Amirhossein Sahebkar; Hassan Rakhshandeh; Vahid Reza Askari (Korean Pharmacopuncture Institute, 2018)
Averagely 80% to 90% of breastfeeding women experience the nipple pain and fissures. The important factor for successful breastfeeding is to treat this problem. This study has done as a review with the aim of analysis of the clinical trials in the field of the prevention and treatment of the nipple fissures and pain due to the importance of breastfeeding. For this purpose, the key words of sore, nipples, fissure, trauma, wound, prevention, treatment, therapeutics, therapy, clinical trial, breastfeeding and their Persian synonyms and all of their possible combinations were searched in the national databases: SID and Iran Medex and Magiran, and in the international databases: PubMed, Scopus, Medline, Science direct by May 2017. The Jadad criterion was used to assess the quality of the articles and the articles with a score of 3 or more were included in this study. Finally, 48 clinical trials were reviewed that 17 of them (sample size 1801) scored 3 or more based on the Jadad criterion. Seven articles were also in the non- drug treatment group (sample size 491) and 2 articles in the drug treatment group (sample size 337) and 8 articles in the herbal treatment group (sample size 973).The results show that menthol and warm water compress as well as teaching the correct breastfeeding methods are effective treatments to prevent and treat the nipple pain and fissures. Moreover, applying the herbal medicine for prevention and treatment of the issues raised from breastfeeding may have beneficial such as Aloe vera, Portulaca olearacea. However, more studies with a great methodology are necessary to obtain more accurate evidence.